PENERAPAN RESTORATIVE JUSTICE DALAM UPAYA DIVERSI TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK - Ferdin Okta Wardana; Danang Wahyu Muhammad; Muhammad Al Ikhwan Bintarto (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
ABSTRACT The crime of theft that often occurs in society is not only committed by adults but also children. The purpose of this study is to find out the factors that cause children to commit theft, how to apply restorative justice to crimes committed by children and what the future concept will be so that the diversion process runs properly. The method used is normative juridical through a statutory approach. The legal materials consist of the 1945 Constitution, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Secondary materials consist of books, journals related to research. The data processing technique is obtained from primary and secondary legal materials which are processed in such a way as to be used as material to be studied. The finished data analysis is carried out as an effort to find and organize systematically in order to increase understanding of the subject matter studied. The results of this study are factors that cause children to steal because of endogenous factors from within themselves besides factors from the family and the surrounding environment that can influence children to steal and the last is economic factors and mass media, in addition to the application of restorative justice for criminal acts. theft committed by children is contained in Article 7 of Law Number 11 of 2012 concerning the juvenile criminal justice system, but in the Act on the juvenile criminal justice system there are several articles that are considered harmful, therefore for the future concept that the rules are changed so that everything is fair not only the perpetrators but also all the injured parties.